Onvansertib exhibits anti-proliferative and anti-invasive effects in endometrial cancer - Sinha, Nikita; Shen, Xiaochang; Haag, Jennifer; Chen, Shuning; Zhang, Haomeng; John, Catherine; Sun, Wenchuan; Emanuele, Michael; Zhou, Chunxiao; Bae-Jump, Victoria (Frontiers in Pharmacology, 2025)
Polo-like kinase 1 (Plk1) is widely recognized as an oncogene that promotes cell proliferation by regulating cell division, DNA damage response, and genome stability and has been shown to be overexpressed in many cancers, including endometrial cancer. Targeting Plk1 by onvansertib has been shown to have anti-tumor activity in pre-clinical models of multiple cancers and is currently being evaluated in phase 1 and 2 clinical trials in cancer patients. In this study, we evaluated the potential anti-tumorigenic effects of onvansertib in endometrial cancer cells and the LKB1fl/fl p53fl/fl mouse model of endometrial cancer. Onvansertib inhibited cellular proliferation, caused G2 phase arrest, induced cellular stress and apoptosis, and inhibited cellular migration and invasion in endometrial cancer cells. Combined treatment with onvansertib and paclitaxel led to synergistic inhibition of cell proliferation. Onvansertib treatment for 4 weeks significantly reduced tumor growth in LKB1fl/flp53fl/fl mice. Given these promising pre-clinical results, further studies are needed to evaluate the clinical translatability of onvansertib combined with paclitaxel as an effective treatment for endometrial cancer.